2015
DOI: 10.1364/ao.54.006690
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of optical vortex beams

Abstract: We show, both theoretically and experimentally, that the propagation of optical vortices in free space can be analyzed by using the width [w(z)] of the host Gaussian beam and the inner and outer radii of the vortex beam at the source plane (z=0) as defined in [Opt. Lett.39, 4364 (2014)10.1364/OL.39.004364OPLEDP0146-9592]. We also studied the divergence of vortex beams, considered as the rate of change of inner or outer radius with the propagation distance (z), and found that it varies with the order in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…2(b), the ring radius-to-width ratio r 0 /ω 0 increases linearly with increasing the OV TC, although the growth rate can be expected to depend on the used device (mode convertor or SLM; see e.g. 53,54 and the references therein). In www.nature.com/scientificreports/ our case, for TCs between 2 and 6, we always observed decay of the multiple-charged vortex state into singlycharged OVs leading to an irregular modulation of the background Gaussian beam.…”
Section: Resultsmentioning
confidence: 99%
“…2(b), the ring radius-to-width ratio r 0 /ω 0 increases linearly with increasing the OV TC, although the growth rate can be expected to depend on the used device (mode convertor or SLM; see e.g. 53,54 and the references therein). In www.nature.com/scientificreports/ our case, for TCs between 2 and 6, we always observed decay of the multiple-charged vortex state into singlycharged OVs leading to an irregular modulation of the background Gaussian beam.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the knowledge of OAM beams divergence is necessary for a proper design of the system of lenses for OAM beam collimation and transmission. So far the divergence of OAM beams has been investigated, focusing on the generation of OAM beams from a Gaussian beam, both theoretically [20] and experimentally [21,22] with a set of four OAM modes. Nevertheless, the divergence of optical vortices emitted by integrated microrings have not been thoroughly investigated yet.…”
Section: Gaussianmentioning
confidence: 99%
“…Orbial angular momentum (OAM) vortex beams have orthogonality of modes due to its spiral phase wave-front, which can be used to improve wireless communication capacity and radar detection capabilities. [1][2][3][4] As early as 1992, Allen et al found that Laguerre-Gaussian (LG) beams carrying spiral phase factors of exp(jlϕ), with orthogonality between different modes l. 5 Inspired by the successful application of optical vortex, [6][7][8] OAM vortex wave was considered extending from optics to radiofrequency. Since Bo Thidé et al proposed radio vortex waves which are effectively generated by array antennas, the study of OAM in microwave frequency band has become a hot topic.…”
Section: Introductionmentioning
confidence: 99%